PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI PEMODERASI - Alfiatul Maulida; Ratih Kusumawardhani; Inosensius Basenti Lusi Betekeneng (Jurnal Akuntansi Dan Manajemen, 2023)
The purpose of this study was to test whether the effect of financial performance has a positive effect on firm value with corporate social responsibility as a moderator. The population in this study used 30 food and beverage companies listed on the IDX during the 2019-2022 period. The sample used in writing this research was purposive sampling. Data obtained from 30 food and beverage companies listed on the IDX during the 2019-2022 period were processed using SPSS 23. The results of this study indicate that financial performance has a positive effect on company value and corporate social responsibility is able to moderate these two variables.